2007
DOI: 10.1074/jbc.m704788200
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium Scanning in an Enzyme Active Site

Abstract: The aminoacyl-tRNA synthetases (aaRSs) 3 play a crucial role in preserving the accuracy of genetic code translation, linking each amino acid to a cognate tRNA, which carries the corresponding anticodon. Each of the 20 aaRSs must bind its target amino acid substrate with a high specificity (1-8). In the "class IIb" subgroup, formed of AspRS (9 -16, 21-26), AsnRS (17,24),25), a network of electrostatic interactions ensures binding specificity for the cognate amino acid side chain in each case. Experimental and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 60 publications
2
14
0
Order By: Relevance
“…This also shows that the absolute configuration of the amino acid is not required for recognition inside the active site of AspRS, and most probably the same holds for other aaRSs. This finding matches with the results of Thompson et al [24] who concluded that there is only limited chiral specificity for L-Asp, leading to an esterification of (D)-Asp to tRNA Asp with a rate of 1:4000 for (D)-Asp vs (L)-Asp.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This also shows that the absolute configuration of the amino acid is not required for recognition inside the active site of AspRS, and most probably the same holds for other aaRSs. This finding matches with the results of Thompson et al [24] who concluded that there is only limited chiral specificity for L-Asp, leading to an esterification of (D)-Asp to tRNA Asp with a rate of 1:4000 for (D)-Asp vs (L)-Asp.…”
Section: Discussionsupporting
confidence: 92%
“…From their [24]theoretical studies they concluded that the network of electrostatic interactions between the incoming amino acid, ATP and the synthetase are highly unfavorable for incorporation of a (D)-amino acid. Not only in the aminoacylation step (relevant for our studies), but likewise in the peptide bond formation reactions, it would be virtually impossible to incorporate (D)-amino acids in protein structures.…”
Section: Discussionmentioning
confidence: 99%
“…Recently published molecular dynamics simulations predict that the free energy difference between the binding of L-and D-tyrosine to E. coli tyrosyl-tRNA synthetase is 13 (Ϯ8) kJ/mol (41). Both our results and those of Thompson et al (41) are close to the experimentally determined free energy difference for the binding of L-and D-tyrosine (⌬⌬G 0 ϭ 5.0 kJ/mol).…”
Section: Discussionsupporting
confidence: 78%
“…6 7 The residues composing the nanospace of the active site stabilize the substrates and favor the progress of the reaction by catalysis. 8 Extensive studies about the active site of aaRSs are carried out, principally using crystallographic methods complemented by biochemical methods, spectroscopic studies, computer simulations [33][34][35][36][37][38][39][40] and electronic structure based analysis. [41][42][43][44][45][46] Despite the wealth of information, the understanding of the principles controlling the organization of the active sites is yet to be completed.…”
Section: Introductionmentioning
confidence: 99%